The Students’ Perception on the Use of TikTok Application at Jakarta International University - Mutiara, Ruth; Dewi Rosari, Maria (English Education:Journal of English Teaching and Research, 2024)
Nowadays, social media like TikTok is utilized for various purposes. It is used for entertainment and educational purposes. That is why, many English learners used TikTok to learn English, specifically English pronunciation. This study aims to find the students’ perception of learning English pronunciation through the TikTok application. In order to find the students’ perception, the researchers used qualitative method by involving 16 first-year students majoring in English literature.Then a questionnaire consisting of 13 open-ended questions was used to collect the data. The findings indicated that most participants showed positive perceptions as they enjoyed learning English pronunciation through TikTok since it was fun, stress-relieving, and convenient. Moreover, they experienced an improvement in their pronunciation skill and thus, most of them agree that TikTok can be an effective learning method to learn English pronunciation.